Profile of vegetarian customers of a university restaurant of Vitória-ES (Research, Society and Development, 2021)
This study aimed to assess the sociodemographic profile, eating habits and knowledge of nutrition of vegetarian customers in a university restaurant. This is a cross-sectional study carried out with 3348 customers of a collective feeding establishment linked to a higher education institution in Vitória-ES, of which 196 were vegetarians. A semi-structured questionnaire was used with questions about sociodemographic profile, eating habits and knowledge about nutrition. The data were analyzed in SPSS, adopting p